German Contribution to Archeological Study of the Golden Horde Ukek: A Review of Ethnographic Sources - Oksana V. Matasova (Publishing house "Sreda", 2020)
The article presents a chronological overview of the study of the Uvek settlement. Arguably one of the oldest cities and major political and economic centers of the Golden Horde, Ukek stood at the intersection of the Northern branch of the Great Silk Road and the Great Volga Trade Route, providing trade caravans and embassies a safe way across the Volga on their further journey to the Crimea or Scandinavia. It is noted that having been weakened by the decline of trade and the plague outbreak, Ukek was completely destroyed by Tamerlane and soon forgotten. It is safe to say that much of the credit for conducting research of that archaeological site belongs to researchers from countries other than Russia. The aim of the article is to reveal the role of German researchers in the study of Ukek. Methods of research. The author provides a timeline of the research of the Uvek archaeological site carried out by German archeologists. Having consulted various sources, primarily academic papers, the author has been able to collect information about the German researchers of Ukek and analyze their academic contribution. It is noted that the first scientific publication about Ukek was published in German as German researchers revealed the connection between Ukek and the Uvek settlement and started the first excavations there. As a result of the analysis, the article concludes that German archeologists, being at the origins of the research of the Uvek archaeological site, contributed to the formation of the traditions of the archeological schools of Volga region. The author emphasizes that the course of the study of the Ukek heritage is important for understanding the cultural and historical processes in the Volga region that facilitated academic links between this region and Europe.